Field notes contributed by James L. Hansen, spring 1986 - Hansen, James L.et al (1986)
List of birds and locations contributed by James L. Hansen with observers Ron Andrews, Lowell Washburn and others. This item was submitted past the deadline for the Iowa Ornithologists Union Quarterly field report of spring 1986. Epson - sheet feed